Sculpting Hope: Exploring Challenges, innovations and Future Horizons in treatment of Pelvic Bone Sarcomas (Journal of Pakistan Orthopaedic Association, 2024)
Musculoskeletal tumors of the Pelvis can either be Primary Bone tumors or Metastatic Lesions. The most frequent are Osteosarcomas, Ewings Sarcoma, Chondrosarcoma, and Metastatic carcinoma. The field of Pelvic Oncological surgery has advanced in recent years due to the progress in Anesthesia, Peri-Operative care, and Improved Imaging capabilities, particularly the use of Computed Tomography (CT), Magnetic Resonance Imaging (MRI), and the development of adjuvant chemo and radiotherapy.  Pelvic sarcomas are typically a challenge when it comes to resection of these tumors, this is multifactorial, like proximity of the tumor to the Genitourinary structures, adjacent neurovascular bundles, size of the tumor, difficult anatomy of the Pelvis, high level of surgical skills required for resection and reconstruction and associated high morbidity and mortality with Pelvic Surgeries.